Socioeconomic inequalities in depression and the role of job conditions in China - Ma, Jie; Wu, Jinjing; Marois, Guillaume (Frontiers in Public Health, 2024)
BackgroundThe rising prevalence of depression in China, coupled with a tightening job market, highlights concern for the workforce’s mental health. Although socioeconomic inequalities in depression have been well documented in high-income countries, the association between socioeconomic status (SES) and depression, along with its work-related mediators, has not been sufficiently studied in China.MethodsThe study participants are 6,536 non-agriculturally employed working adults from the 2020 China Family Panel Studies (CFPS). We build linear regression models to examine the relationship between SES and depression, using education and income as indicators of SES. We also apply a framework based on seemingly unrelated estimation (SUEST) to assess how job conditions, which include job demands and job resources, mediate this relationship.ResultsBoth education and income are negatively associated with depression, with education’s association with depression remaining net of income. Mediation analysis reveals that the well-educated tend to occupy less demanding work with shorter working hours and lower probability of on-call duty, which partially helps explain the education-based depression gap. Higher earners experience more demanding work with longer working hours and higher probability of on-call duty, which potentially masks the income-based depression gap. Greater job resources including moderate schedule flexibility and better job security, appear to contribute to explaining the depression gap across SES.LimitationThe cross-sectional design of this study precludes causal inferences. Not all typical job demands and resources could be included due to data limitations.ConclusionOur study provides insights into socioeconomic inequalities in mental health in the Chinese working population, with implications for policies aimed at preventing depression and improving mental health equity.